Effects of a mindfulness‐based weight loss intervention in adults with obesity: A randomized clinical trial. Issue 4 (9th March 2016) - Daubenmier, Jennifer; Moran, Patricia J.; Kristeller, Jean; Acree, Michael; Bacchetti, Peter; Kemeny, Margaret E.; Dallman, Mary; Lustig, Robert H.; Grunfeld, Carl; Nixon, Douglas F.; Milush, Jeffrey M.; Goldman, Veronica; et al.
Abstract : Objective: To determine whether adding mindfulness‐based eating and stress management practices to a diet‐exercise program improves weight loss and metabolic syndrome components. Methods: In this study 194 adults with obesity were randomized to a 5.5‐month program with or without mindfulness training and identical diet‐exercise guidelines. Intention‐to‐treat analyses with multiple imputation were used for missing data. The primary outcome was 18‐month weight change. Results: Estimated effects comparing the mindfulness to control arm favored the mindfulness arm in (a) weight loss at 12 months, −1.9 kg (95% CI: −4.5, 0.8; P  = 0.17), and 18 months, −1.7 kg (95% CI: −4.7, 1.2; P  = 0.24), though not statistically significant; (b) changes in fasting glucose at 12 months, −3.1 mg/dl (95% CI: −6.3, 0.1; P  = 0.06), and 18 months, −4.1 mg/dl (95% CI: −7.3, −0.9; P  = 0.01); and (c) changes in triglyceride/HDL ratio at 12 months, −0.57 (95% CI: −0.95, −0.18; P  = 0.004), and 18 months, −0.36 (95% CI: −0.74, 0.03; P  = 0.07). Estimates for other metabolic risk factors were not statistically significant, including waist circumference, blood pressure, and C‐reactive protein. Conclusions: Mindfulness enhancements to a diet‐exercise program did not show substantial weight loss benefit but may promote long‐term improvement in some aspects of metabolic health in obesity that requires further study.